DEPRESSION AND INTERNET GAMING DISORDER AMONG MEDICAL STUDENT IN MALANG, INDONESIA - Kurnianingsih, Nia; Cahayani, Wike Astrid; Yudhantara, Dearisa Surya; Ratnawati, Retty (MNJ (Malang Neurology Journal), 2025)
Background: Medical education is widely regarded as a highly demanding curriculum that causes significant stress among students. Chronis stress generates depression and increase of internet gaming activity. Previous research examined the relationship between the length of time spent for internet gaming activity as well as grade point average (GPA) towards internet gaming disorder (IGD) among medical student in Malang Indonesia. The limited data on the frequency of depression and the association between depression with IGD among medical students calls for more research. Objectives: This study was purposed to analyse the prevalence of depression as well as its association with IGD among medical students in Malang, Indonesia. Methods: This descriptive and cross-sectional study involved 437 medical students who completed a set of self-report questionnaires. The questionnaires included sociodemographic data, Beck Depression Inventory (BDI) scale and Personal Internet Gaming Disorder-9 (PIE-). Descriptive and bivariate analyses were employed for statistical analysis. Results: Depression was identified among 37.99% students, with female being more likely to suffer from it. There were 59.64%, 34.94% and 5.42% correspondingly of students with mild, moderate, and severe depression. The rate of depression was highest among 1st year students. Poor GPA achievement was observed in 50.98% of students with depression. Students without internal motivation were more likely to have depression (57.14%). Surprisingly, depression was not linked associated with IGD (p=0.06). Conclusion: This study concluded a high prevalence of depression among medical students with various sociodemographic characteristics. Despite depression had no association with IGD, future research is necessary for evaluate the potential risk factor of depression among medical students.